Molecular characterization of the porcine reproductive and respiratory syndrome (PRRS) of the nucleocapsid gene ORF 7 in pig farms in Lima, Perú - Cotaquispe Nalvarte, Rony (2022)
The Betaarterivirus suid 1 and Betaarterivirus suid 2 species of the Porcine Reproductive and Respiratory Syndrome (PRRS) virus cause severe outbreaks due to genetic recombination with high epidemiological risk, which requires rapid identification for efficient molecular epidemiological surveillance. The objectives of the study were the analysis of the gene that synthesizes the nucleocapsid proteins (ORF 7), as well as to determine the phylogenetic relationships with specific primers. Molecular characterization was performed and 24 positive isolates of the Betaarterivirus suid 2 species were identified. Ten isolates were genotyped, relating 8 of them to lineage 1: sublineage 1.5 with the representative variant NADC34 and 2 to lineage 5: sublineage 5.1 with the representative variant RespPRRS_MLV. In addition, the molecular homology test was performed with the DNAMAN program on the 10 isolates, obtaining 99% (8) and 87% (2) of similarity with the NADC34 variant, confirming the aforementioned. The phylogenetic relationship with the reported isolates and the results obtained indicate that at least 10 belonged to the Betaarterivirus suid 2 species through the nucleocapsid gene (ORF 7) with the research's own primers and the parental relationship of 8 isolates with lineage 1: sublineage 1.5 and 2 isolated with lineage 5: sublineage 5.1 of the species Betaarterivirus suid 2.